2020
DOI: 10.1007/s11027-020-09924-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the relationship between carbon emission performance and urbanization: evidence from China

Abstract: Global change caused by carbon emissions alone has become a common challenge for all countries. However, current debates about urbanization and carbon emissions generally do not take into account the heterogeneities in urbanization and economic development levels. The goal of this study is to revisit the urbanizationemissions nexus by considering such heterogeneities in the Chinese context. The results reveal that there is significant heterogeneity in the total factor carbon emission performance index across p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 64 publications
5
11
0
Order By: Relevance
“…Meanwhile, Wang et al (2016) consider BRICS economies and confirm a panel causality between urbanization and CO2 emission, whereas Wang et al (2015) show that urbanization significantly contributes towards change in the value of per capita carbon emission. Besides, some other studies have confirmed that both urbanization and carbon emission is significantly linked with each other Shah et al 2020;Shi and Li 2018;Sun and Huang 2020;Zhao et al 2020;Zhou et al 2021).…”
Section: Resultsmentioning
confidence: 87%
“…Meanwhile, Wang et al (2016) consider BRICS economies and confirm a panel causality between urbanization and CO2 emission, whereas Wang et al (2015) show that urbanization significantly contributes towards change in the value of per capita carbon emission. Besides, some other studies have confirmed that both urbanization and carbon emission is significantly linked with each other Shah et al 2020;Shi and Li 2018;Sun and Huang 2020;Zhao et al 2020;Zhou et al 2021).…”
Section: Resultsmentioning
confidence: 87%
“…Second, urbanization improves the utilization rate of public facilities and transportation, forms an industrial agglomeration, and then reduces the cost of pollution treatment, which is conducive to reducing pollution emissions. Third, more studies believe that the relationship between urbanization and air pollution is nonlinear, such as inverted U, N-shaped or U-shaped, etc (e.g., Zhao et al, 2020). Therefore, we do not prejudge the effect of urbanization on air quality.…”
Section: Variables and Methodsmentioning
confidence: 88%
“…After a certain stage of urban development, with the improvement of people's environmental awareness, the strictness of social regulation requirements on the environment, and the upgrading of the city's leading industries from the manufacturing industry to the service industry, the degree of air pollution may decline (Zhao et al, 2020). Chinese new urbanization strategy launched in 2014 is not a policy specifically designed to affect air quality but compared with the past urbanization, there are obvious differences in energy utilization and environmental protection because the new urbanization puts forward high requirements in terms of green and low-carbon transformation development and controlling the size of the urban population through four channels: intensive urbanization, intelligent urbanization, green urbanization, and low-carbon urbanization.…”
Section: Relationship Between New Urbanization and Air Qualitymentioning
confidence: 99%
“…The rapid economic growth has been accompanied by a significant increase in energy consumption and greenhouse gas (GHG) emissions (An et al, 2021). Since 2006, China has become the world's largest emitter of carbon dioxide (Zhao et al, 2020), and the issue of GHG emission reduction has become a growing concern. Considering the deteriorating environment and the consequential international pressure, the Chinese government has developed an ambitious GHG reduction plan (Cheong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%